Study the Impact of Surface Roughness on the Flow Characteristics at the Downstream of a Broad-Crested Weir - Ali Al-Ridha Jaafar Razzaq; Baneen Ahmed Hussein (American Journal of Biomedicine and Pharmacy, 2025)
Weir is usually incorporated as a control or regulation device in hydraulic systems, with flow measurement as their secondary. It is normally intended for use in the field and thus to regulate broad discharges. Broad-Crested weir is among the oldest common weir types. In this paper, the effect of height and surface roughness for different Board Crested weirs models were studied on discharge coefficient (Cd) in a horizontal open channel. In the crest of the weir, certain materials may be combined with concrete (e.g., boulders) or may be used as cladding to minimize the effect of water overflow (e.g. stone). The weir surface should not be considered smooth in this case, and the discharge coefficient (Cd) must be re-estimated. For these purposes, laboratory flume was used to study the effect of height and surface roughness on the discharge coefficients with six of the different broad crested weirs models dimensions of the concrete blocks. In this study, the flow conditions were considered to be free water flow and the viscosity effect was neglected. The results showed that the discharge coefficient Cd decreases as the increasing roughness of the broad weir crest surface for a given (H/H+P). The discharge coefficient Cd increases with increased (H/H+P). For group 1, the average value of the discharge coefficient was 0.66, 0.65, and 0.64 in the case of a smooth surface (case 1), in the case of a rough surface covered by gravel (case 2), and in the case of a rough surface covered by boulders (case 3), respectively. For compassion between cases 1 and 2, and also between cases 1 and 3, the percentage of a decrease in coefficient of discharge was around 2% and 3.5%, respectively. For group 2, the average value of the discharge coefficient was 0.63, 0.62 and 0.61 in the case of a smooth surface (case 4), in the case of a rough surface covered by gravel (case 5) and in the case of a rough surface covered by boulders (case 6), respectively. For compassion between cases 4 and 5, and also between cases 4 and 6, the percentage of a decrease in coefficient of discharge was around 1.75% and 3%, respectively. The best curve-fit equations have been created.